Querying Childhood: Feminist Reframings (Politics and Society in India and the Global South, 2025)
This book critically examines assumptions about age, women, and gender. Amidst all the attention that has been granted to difference and inequality, however uneven and unsatisfactory in terms of class and caste, race and ethnicity, sexuality and gender, disability, religion, and nation, questions of age and its importance for feminism have been less well defined. Drawing on recent literature on childhood, the chapters in this volume cover a range of fresh perspectives. These include: What kinds of biological, legal, chronological histories age has and the fundamental ways in which these links are being recast How gender differences occupy a prominent place in historical constructions of identities, especially the frequent infantilisation of women, who are never seen as adults in the full sense of the term nor equally allowed to be children beyond the first years of life Ways in which class, caste, gender, and ethnicity shaped classrooms and opportunities for education in the colonial period and the 20th century to produce new ideas of childhood Gendered outcomes for children in the context of a long entanglement of law with labour, transformations in practices of parenting over time, and how the concept of care emerged in both Western and non-Western societies An incisive study on how childhoods have come to be understood, this book will be of great interest to scholars and researchers of gender studies, childhood studies, family studies, modern history, legal history, social policy, social psychology, education, and sociology. This volume will also interest parents, paediatricians, family health providers, teachers and educators, and anyone who works with children.